Material Exchange and Migration between Pore Fluids and Sandstones during Diagenetic Processes in Rift Basins: A Case Study Based on Analysis of Diagenetic Products in Dongying Sag, Bohai Bay Basin, East China. (15th February 2018) - Meng, W.; Zeng, J. H.; Cao, Z.; Song, G. Q.; Wang, Y. S.; Teng, J. L.; Guo, Z.
Abstract : The exchange and migration of basin materials that are carried by pore fluids are the essence of diagenesis, which can alter physical properties of clastic rocks as well as control formation and distribution of favorable reservoirs of petroliferous basins. Diagenetic products and pore fluids, resulting from migration and exchange of basin materials, can be used to deduce those processes. In this study, 300 core samples from 46 wells were collected for preparation of casting thin sections, SEM, BSE, EDS, inclusion analysis, and isotope analysis in Dongying Sag, Bohai Bay Basin, East China. Combined with geochemical characteristics of pore fluids and geological background of the study area, the source and exchange mechanisms of materials in the pore fluids of rift basins were discussed. It was revealed that the material exchange of pore fluids could be divided into five stages. The first stage was the evaporation concentration stage during which mainlyC a 2 +, M g 2 +, andC O 3 2 - precipitated as high-Mg calcites. Then came the shale compaction stage, when mainlyC a 2 + andC O 3 2 - from shale compaction water precipitated as calcites. The third stage was the carboxylic acid dissolution stage featured by predominant dissolution of plagioclases, during whichC a 2 + andN a + entered pore fluids, and Si and Al also entered pore fluids and then migrated as clathrates, ultimately precipitating as kaolinites. The fourth stage was the organicC O 2 stage, mainly characterized by the kaolinization of K-feldspar as well as dissolution of metamorphic lithic fragments and carbon cements. During this stage, K +, F e 2 +, M g 2 +, C a 2 +, H C O 3 -, andC O 3 2 - entered pore fluids. The fifth stage was the alkaline fluid stage, during which the cementation of ferro-carbonates and ankerites as well as illitization or chloritization of kaolinites prevailed, leading to the precipitation ofK +, F e 2 +, M g 2 +, C a 2 +, andC O 3 2 - from pore fluids.